THE ECONOMIC IMPACT OF THE ABOLITION OF THE MILK QUOTA REGIME ON THE ROMANIAN DAIRY SECTOR - Silviu STANCIU (Network Intelligence Studies, 2015)

(untitled)
Animal breeding for milk represents a basic occupation of the Romanian population, ensuring the best utilization of fodder obtained from natural pastures, steady incomes and local workforce stability. Since 2015 the restrictions imposed to producers from the European Union by the Milk Quota System ceased. The implementation of government strategies to support the national level of production and to efficiently capitalize raw milk and consumption could ensure a healthy nutrition to the population and substantial income. Romanian producers are affected by the quota’s elimination, which overlapped with a decrease in sales by increasing the milk supply on the domestic market due to Russia’s embargo.